Cross-Examining the Computer: Uncertainty in the Court - John McClellan Marshall (Studia Iuridica Lublinensia, 2023)
This paper is intended to provide lawyers, young and old, with an analytical approach to their practice that is perhaps broader than they originally learned in law school or as young associates. Because lawyers and judges tend to be derived in large part from the liberal arts, this approach broadens that view borrowed in part on the principles of quantum mechanics, in particular Heisenberg’s “uncertainty principle.” While lawyers and judges are accustomed to some level of uncertainty, whether in an office context or at trial, the question of how to deal with it varies quite widely from person to person, and the subjectivity itself creates problems. Admittedly, this is an exercise in the “intellectual aspects of the practice of law,” which is an eminently practical activity, but it is intended to raise questions as to the role of modern technology in the legal context, as well as provide, to some extent, answers.